Production Analysis and Allocative Efficiency of Rice Farming - La Iwe; Yuli Purbaningsih; Suparman Suparman; Irwansyah Irwansyah (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
This study aims to determine the influence of production factors on production and the allocative efficiency of using production factors in rice farming in Tampabulu Village, North Poleang District, Bombana Regency. The sample in this study was determined using the Slovin method, while the data analysis method employed was multiple linear regression analysis with the Cobb-Douglas function and allocative efficiency analysis. The results indicate that the use of production inputs such as land area, urea fertilizer, organic fertilizer, and seeds significantly affects production. In contrast, the use of labor, KCL fertilizer, and pesticides does not significantly affect rice farming production. The use of production inputs like land, urea fertilizer, KCL fertilizer, and organic fertilizer is not yet efficient, as indicated by an NPMX/Px value greater than 1, suggesting that these inputs should be increased. Conversely, the use of labor, pesticides, and seeds in rice farming is inefficient, as shown by an NPMX/Px value of less than 1, indicating that these inputs should be reduced to achieve optimal usage.